“Islamic state”: ideology, structure, military and political activities - A. Vavilov (Международная аналитика)
The article atempts to retrace the establishment of the terrorist group “Islamic State” (IS, ISIS) by analyzing its structure, ideological and propaganda pratices, economic foundation and sources of recruitment.